Keutamaan Siwak dalam Sholat: Studi Takhrij dan Syarah Hadis - Jihan Zaki; Susanti Vera; Saifudin Nur; Busro (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith regarding the virtue of siwak in prayer through the study of takhrij and syarah hadith. This research method uses a qualitative approach with literature studies related to contemporary analysis. The results of this study found that the hadith about the virtue of siwak in prayer is authentic in terms of sanad and matan. The discussion of this research that the Messenger of Allah, said if I was not worried about burdening the believers, I would have ordered them to sing each time they would pray. It is very clear that the Messenger of Allah ordered to siwak before praying and everything that was ordered by the Messenger of Allah was definitely a benefit. This research is expected to provide benefits, especially for Muslims that before praying it is sunnah to have siwak.